Perceptions of Red Tape by Police Personnel in Different Echelon in Royal Malaysia Police - Mohd Syukry, Mohd Ali (2009)
Red tape is one of the importance fundamental studies of organizations. It has received scant attention from organizational scholars. In particular, this study focuses on managers’ perceptions of red tape between different echelons in organization. Red tape consists of the general administrative red tape and personnel red tape. One model which consist of three main elements for explaining perceptions of red tape are proposed in this study. The job factor model focuses on the factors which influence the performance of the job given which closely related to three hypotheses which are goal ambiguity, insecurity and expectancy.The hypotheses included a goal ambiguity hypothesis that claims that ambiguous goals in the public sector cause managers to create red tape, an insecurity hypothesis that argues that public managers initiate red tape because they feel risk-averse and insecure about their authority and an expectancy hypothesis that depicts red tape as the result of weak linkages between performance and extrinsic rewards such as pay and promotion in the public sector. The data for this study were collected through handing out the questionnaire designated target respondents.The findings indicate that the model is supported. There is a positive moderate relationship between goal ambiguity, insecurity, expectancy over red tape. Middle level rank police personnel perceived higher red tape as compared to lower level rank police personnel. Finally, police personnel in Royal Malaysia Police perceived higher level personnel red tape rather than general administrative red tape.